Analisis Bahan Gerabah Pada Temuan Hasil Ekskavasi di Kawasan Lembah Behoa - Triningsih, Wiji; Umar, Dwi Yani Yuniawati (KALPATARU, 2022)
The Behoa Valley Area is one of megalithic cultural heritage from the early metal era (paleometallic) and the supporting communities was already familiar with technology of pottery creation. The discovery of pottery fragments dominates each research carried out in this site. This paper aims to understand the source of the pottery materials by comparing modern pottery materials used by the current community around the site. Total of 26 samples were used, consist of 24 pottery fragments sampled from sites in The Behoa Valley area, one pottery fragment sampled from Pangawumbu, and one pottery fragment sampled from craftsman in Doda village. Method of analysis used in this research is chemical element analysis, conducted towards the clay matrix and carried out microscopically using Scanning Electron Microscope (SEM). Chemical element analysis of the clay matrix are used to understand the pottery clusters based on chemical element composition contained in the clay matrix. Pottery clusters then discovered from statistical analysis using Principal Component Analysis and Hierarchical Clustering Analysis methods. Based on the result of the chemical elements analysis, it is revealed that pottery material from the sites in The Behoa Valley area has similarity with pottery material from craftsman around the site.